Rancang Bangun Aplikasi Presensi Siswa Berbasis Mobile (Android) untuk Efisiensi Pemantauan Kehadiran di SDN Tegal Pagedangan - Riski Putra Al Hakim; Farizi Ilham; Azfi Muhajir; Syahril Jihad (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
The student attendance recording process at SDN Tegal Pagedangan has been conducted manually using physical attendance books, which are susceptible to data damage, difficult recapitulation, and lack of information transparency for parents. This study designs and develops a mobile-based (Android) student attendance application using the Kotlin programming language integrated with a MySQL database through a RESTful API, employing the Waterfall development methodology. Key features include role-based authentication (Admin, Teacher, Student), QR Code scanning for attendance recording, attendance recapitulation, digital leave submission, and an automatic reporting dashboard. Black Box Testing was conducted across all functional scenarios with a 100% success rate. The application implementation has proven to accelerate the attendance process by more than 60%, minimize human error, and facilitate real-time attendance monitoring by school staff and parents.